About the feasibility of transactional support in cloud computing (fast abstract) - Maia, Francisco (2010)
In this paper we review what it has been stated so far about transactional support on the cloud computing environment. Then, we propose to extend them with some ideas already stated in replicated databases, like the certification process, to solve certain problems about coordination in the commit phase of transactions in the cloud.